Kualitas Pembelajaran Pada Media Pembelajaran - Suprihadi, Suprihadi (Fakultas Ekonomi Universitas Gresik, 2023)
In Indonesia, Corona Virus Disease (Covid-19) was first reported on March 2, 2020 due to the rapid transmission until the end of May 2020, the Covid -19 outbreak had a direct impact on people's survival and from that moment on, the Indonesian Government directly imposed restrictions community activities in public spaces that result in normal community activities taking place into activities that are not normal and have an impact on work activities both in the government and private sectors that must be carried out at home (work from home).Likewise learning activities in educational institutions for all levels of education must be carried out at home (work from home). achievement of set instructional goals. Online learning is carried out with the support of information technology as a learning medium through zoom, google meet and WhatsApp as a means of communication in implementing the teaching and learning process academically.This research was carried out during the Covid 19 pandemic and during the Covid 19 endemic period which had the goal that online learning remained of high quality if the set instructional goals were achieved and proved that online learning was fun or unpleasant in its implementation after the Covid 19 pandemic for students.